The empowerment strategy for prostitutes through competency-based culinary skills training at Semarang Rehabilitation Center - Hartadi, Sri; Fakhruddin, Fakhruddin; Utsman, Utsman (JPPM (Jurnal Pendidikan dan Pemberdayaan Masyarakat), 2019)
Prostitution is a phenomenon that has existed for a long time in the world, not least in Indonesia. Someone does prostitution most of the problem lies in economic factors and the low skills they have. The government does not remain silent due to this phenomenon, the government has also prepared a variety of skills training programs held in various rehabilitation institution, one of which is in the rehabilitation center of the Semarang city agriculture with empowerment programs through competency-based culinary skills training. The purpose of this study is to describe and analyze the planning, implementation, and results achieved in empowering prostitutes through competency-based culinary skills training. This study uses a qualitative approach. Data collection techniques are carried out by observation, interviews, and documentation. Data analysis techniques include data collection, data reduction, data presentation and conclusion drawing. Check the validity of the data using source triangulation and methods. The results of this study is planning of prostitutes empowerment programs through training in cookery skills includes: identification of needs, formulating learning objectives, determining curriculum to be used, choosing learning resources, and sources of funding. The implementation includes three main steps, namely opening activities, core activities, and closing. The results achieved are that the residents learned how to make steamed sponge, potato donuts, stuffed dumplings, banana chocolate roll omelet.